Russiske kvinner i Nord-Norge: fortellinger om soppturer og Sovjettid - Wara, Tatiana (Nordisk Østforum, 2016)
Published version. Source at http://dx.doi.org/10.17585/nof.v30.430 The article portrays and discusses various reorientation practices used by Russian women who have migrated to the Finnmark region in Northern Norway. It draws on participant observation, individual interviews and focus group interviews. The fieldwork revealed that mushroom related activites picking, talking about, preparing and eating constitute an important part of a shared Russian heritage accumulated through a communist-era childhood. The article makes particular use of Floya Anthias’ concept of translocal positioning. Anthias conceptualizes social positioning as a practice that occurrs within and across both concrete locations and cultural contexts, and is shaped by specific processes of minoritizing and majoritizing. Through the perspective of translocation, and inspired by Merleau-Ponty’s phenomenology of the body (1994), this article aims to show how my informants position themselves as Russian women in Finnmark. Based on an analysis of the experiences and practices related to mushrooms, the article argues that migrants’ reorientations may fruitfully be viewed as practices that are constituted through the body across time and space.